The critical examination of land use management in Mthatha with particular reference to spatial development framework and Integrated Development Plan - Mabusela, Fezeka Faith (University of the Free State, 2008)
The Integrated Development Plan (IDP) of KSD Municipality in relation to spatial planning and land use management is critically examined in this study. The observation made is that the lack of a comprehensive spatial development framework and a clear land use management system for the municipality as part of the municipality's IDP cripples the effective management of land development and use in the area. As Stapelberg (2003: 133) points out, 'the IDPs must be compiled from correct information, with the emphasis on planning and not control. If a municipality has a poorly compiled IDP with a 'bad' SDF, it will not come as a surprise if development does not take place in that municipality as an environment conducive for development will not have been set’. The current systems used for the town planning and land use applications are old and outdated, and a lot of reliance placed on the town planning scheme as a guide in dealing with these applications is greatly criticized, as the town planning scheme is only a development control tool that can never replace the forward planning tool The study further sought to: • Examine the current Town Planning practices in Mthatha and more specifically the Land Use Management in the area and how it is linked with the integrated Development Plan by showing current trends in other municipalities specifically Buffalo City Municipality in the Eastern Cape; • To further establish whether the current Land Use Management tools and strategies used in Mthatha address challenges or objectives of integrated Development Planning. The findings of the study suggested that the Town Planning Scheme or even development control cannot operate in isolation but needs to be part of an Integrated Development Planning for Mthatha. It became evident from the findings of the research that a more flexible land use management tool that would allow for additional and mixed uses in the study area is indeed necessary. It was also the findings of this research that the approach to Land Use Management does not adequately promote the Local Economic Development needs of the area.
Dissertation (M. Sc. (Urban and Regional Planning))--University of the Free State, 2008
Keywords: City Planning -- South Africa -- Umtata; Community development -- South Africa -- Umtata; Land use, Urban -- South Africa -- Umtata